Implementation of Problem Based Learning (PBL) Learning Model to Improve Learning Outcomes of Class VII Students of SMP Negeri 7 Kisaran - Zulfatunisa, Zulfatunisa; Sirait, Syahriani; Manurung, Rumondang F (Holistic Science, 2024)
This study aims to improve students' mathematics learning outcomes by using the Problem Based Learning (PBL) learning model on Algebra material in class VII of SMP N 7 Kisaran. This research is a classroom action research that has been carried out in 2 cycles. The subjects taken were all students of class VII-4 of SMPN 7 Kisaran in the 2024/2025 academic year. Data collection techniques in this study were test techniques and observation results. Based on the results of the study, it can be concluded that the percentage of student learning completion is in the very good category, so it can be said that Problem Based Learning (PBL) is effective for use in algebra material, this is shown in cycle 1 the percentage of learning completion is 70% with an average value of 78.5, and in cycle 2 increased to 90% with an average value of 88.20 In student and teacher activities based on the results of observations also on the model used by researchers, namely Problem Based Learning (PBL) is at an effective level given to students.